Role of sphingolipids in the pathogenesis of intrahepatic cholestasis - Mikucka-Niczyporuk, Agnieszka; Pierzynski, Piotr; Lemancewicz, Adam; Kosinski, Przemyslaw; Charkiewicz, Karol; Knas, Małgorzata; Kacerovsky, Marian; Blachnio-Zabielska, Agnieszka; Laudanski, Piotr (Prostaglandins & other lipid mediators, 2020)
•Intrahepatic cholestasis related perinatal complications include premature birth, meconium-stained amniotic fluid, fetal bradycardia, fetal respiratory distress syndrome and intrauterine fetal demise.•Cholestasis treatment with UDCA is known to be very effective.•Sphingolipids can potentially become screening markers as well as markers for monitoring the treatment of ICP in pregnant women. Intrahepatic cholestasis of pregnancy (ICP) is the most common pregnancy-related liver disorder that affects from 0.2% to 15.6% pregnant women. The disease is connected with increased risk of fetal morbidity and mortality, but is unfortunately detected quite late. The diagnosis of ICP is based on only one manifestation: pruritus which mainly affects soles and palms. Twenty intrahepatic cholestasis of pregnancy (ICP) women and twenty healthy pregnant women (control group) took part in the study. In the study group, blood sampling for baseline measurements was performed on the first day of hospital stay – before the commencement of treatment with ursodeoxycholic acid (UDCA) – and repeated after 7 days of 900 mg UDCA per day. An additional blood sample was collected on the second day after childbirth. In the control group, blood samples were collected directly after hospital admission. We compared plasma sphingolipids in samples of the subjects from ICP and ICP + UDCA-treated groups as well as the ICP group after delivery with the healthy controls. Of all sphingolipids, the median values of C16-Cer and C18-Cer were significantly higher in the plasma of cholestasis patients not treated with UDCA as compared to the control. Following 7 days of UDCA treatment, a considerable decrease in C16-Cer, C18-Cer and the total concentration of bile acids was noted as compared to the baseline. It is known that sphingolipids serve as modulators of liver regeneration. We assume these substances could be potential markers for detecting early onsets of intrahepatic cholestasis of pregnancy.